Morphological Analysis of the Slovak Language - Daniel Hladek; Jan Stas; Josef Juhar (Advances in Electrical and Electronic Engineering, 2015)
This paper proposes a new statistic-based method of segmenting words by identification of a suffix. Ability to identify suffix can improve morphological analysis by allowing the classifier to assign tags to words previously unseen in the training corpus. Identified suffix of the word can be used to improve the accuracy of the part-of-speech tagging or other natural language processing tasks.